Impact of sexual intercourse on frozen-thawed embryo transfer outcomes: a randomized controlled trial - Jin-Wei Hou; Li-Hua Yuan; Xian-Ling Cao; Jing-Yan Song; Zhen-Gao Sun (BMC, 2023)
Abstract Background Exposure of the female reproductive tract to either seminal plasma or fluid component of the ejaculate is beneficial to achieving successful embryo implantation and normal embryo development. But whether the "physical" component of sexual intercourse during the peri-transfer period have any influence on frozen-thawed embryo transfer (FET) pregnancy outcomes is not clear. Methods We conducted a randomized trial that included 223 patients undergoing in vitro fertilization (IVF) treatment at a university-affiliated reproductive center from 19 July 2018 to 24 February 2019. Enrolled patients undergoing IVF treatment were randomized either to engage sexual intercourse using the barrier contraception (Group A, n = 116) or to abstain (Group B, n = 107) one night before FET. The primary outcome was clinical pregnancy rate. Results Patients having intercourse had higher clinical pregnancy rate (51.72% vs. 37.07%, P = 0.045) and implantation rate (38.31% vs. 24.77%, P = 0.005) compared to those did not engage intercourse. However, there was no significant difference of the spontaneous abortion rate between two groups (11.67% 33 vs. 14.63%, P = 0.662). Conclusions Sexual intercourse before embryo transfer may improve the clinical pregnancy and implantation rates during FET cycles. However, it should be noted that patients choose only one time for sexual intercourse, that is, the night before embryo transfer. Trial registration The present study was registered at the Chinese Clinical Trial Registry ( http://www.chictr.org.cn/ , ChiCTR1800017209).